2021
DOI: 10.18231/j.jds.2021.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc lozenge on pain, oedema, and trismus after impacted third molar surgery: A prospective randomized, double-blinded, placebo-controlled study

Abstract: The postoperative sequelae after third molar surgery include pain, swelling and trismus, Zinc acts as anti-inflammatory agent, can promote wound healing, immune system modulation, tissue repair, and significant reduction in the use of analgesics for oral pain. This study was aimed to evaluate the efficacy of oral zinc lozenge given 30 min before surgery on reducing postoperative sequelae.s: We recruited 70 patients, randomly assigned to two groups: Zinc and Control group, groups received 40mg Zinc lozenge, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Continuous medication with NSAIDs is recommended as the first-line treatment after extraction of mandibular third molars to relieve pain and inflammation. Oral administration of NSAIDs can lead to various adverse effects; therefore, topical NSAIDs are preferred to minimize these side effects [ 9 , 27 , 28 ]. The problem with the administration of NSAIDs thrice a day is that the analgesic effect wears off and postextraction pain recurs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous medication with NSAIDs is recommended as the first-line treatment after extraction of mandibular third molars to relieve pain and inflammation. Oral administration of NSAIDs can lead to various adverse effects; therefore, topical NSAIDs are preferred to minimize these side effects [ 9 , 27 , 28 ]. The problem with the administration of NSAIDs thrice a day is that the analgesic effect wears off and postextraction pain recurs.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with gastrointestinal ulcers or aspirin-induced asthma, acetaminophen may be used as an alternative drug [ 4 ]. NSAIDs, such as celecoxib [ 5 , 6 ], valdecoxib [ 7 ], ibuprofen [ 8 ], flurbiprofen [ 9 ], lornoxicam [ 10 ], etoricoxib [ 11 ], and opioid-containing drugs such as oxycodone [ 12 ] have been studied to identify the optimal analgesics for pain relief in mandibular third molar extractions. In a systematic review of 21 high-quality clinical trials, Weil et al reported that oral paracetamol (acetaminophen) was safe and effective in the treatment of postoperative pain after extraction of embedded mandibular third molars [ 13 ], and in a Cochrane review of 2242 patients, Bailey et al reported that oral ibuprofen was superior to oral paracetamol in the treatment of postoperative pain [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with gastrointestinal ulcers or aspirin-induced asthma, acetaminophen may serve as an alternative [ 4 ]. Various NSAIDs, including celecoxib [ 5 , 6 ], valdecoxib [ 7 ], ibuprofen [ 8 ], flurbiprofen [ 9 ], and opioid-containing medications such as oxycodone [ 10 ], have been closely evaluated to identify optimal analgesics for pain alleviation in mandibular third molar extractions. A systematic review by Weil et al highlighted the safety and efficacy of oral paracetamol (acetaminophen) in postoperative pain management after embedded mandibular third molar extractions [ 11 ], whereas the Cochrane review by Bailey et al highlighted the superiority of oral ibuprofen over oral paracetamol in this context [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rindal et al recently outlined a randomized controlled trial protocol to mitigate opioid-related issues, with a focus on interventions to reduce opioid prescriptions in favor of nonopioid alternatives [ 15 ]. Furthermore, topical analgesic application has emerged as a potentially safer approach to enhance postoperative pain relief [ 16 ]; studies have shown reduced side effects without decreases in analgesic efficacy [ 9 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%